A Retrospective Study of the Relationship Between Blood Transfusion and 30-Day Postoperative Outcomes in Patients Undergoing Isolated Off-Pump Coronary Artery Bypass Grafting - Lu,Liangyuan (2022)
ABSTRACT Introduction: The objective of this single-center study it to retrospectively analyze the relationship between transfusion and 30-day postoperative outcomes in patients undergoing isolated off-pump coronary artery bypass grafting. Methods: Perioperative data of 2,178 patients who underwent isolated off-pump coronary artery bypass grafting from 2018 to 2019 were collected. A 1:1 propensity score matching was performed to control for potential biases between patients who received blood transfusion and those who did not. After propensity score matching, we analyzed the clinical outcomes of transfusion and non-transfusion patients. Postoperative complications and the survival of patients within 30 days after surgery in both groups were analyzed. Kaplan-Meier survival curve and log-rank test were used for survival analysis. Results: The total blood transfusion rate of all patients was 29%, including red blood cell (27.6%), plasma (7.3%), and platelet (1.9%). Four hundred and forty patients in each group were compared after propensity score matching. There were no significant differences in the incidence of stroke, myocardial infarction, atrial fibrillation, acute kidney function injury, and sternal wound infection of both groups (P>0.05). However, higher incidence of postoperative pulmonary infection and more mechanical ventilation time and days of stay in the intensive care unit and postoperative in-hospital stay were associated with blood transfusion (P<0.05). The 30-day cumulative survival rate of the transfusion group was lower than that of the control group (P<0.05). Conclusion: Perioperative blood transfusion increases the risks of postoperative pulmonary infection and short-term mortality in off-pump coronary artery bypass grafting patients.